Validity of QR Code e-Module as A Media for Ecosystem Learning - Romadhoni, Dwi Wulan; Wulandari, Tabitha Sri Hartati (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2025)
With the rapid technological growth, education must participate in using technology as an innovation in learning. The purpose of this study is to know the validity of QR code e-Module as a media for ecosystem learning This research is development research using Addie models. The model consists of the five stages of analysis, design, development, implementation, and evaluation. But in this research only to the stage of development. The study was carried out in the month of March-May 2024. The data used in this study is data on the validity of the QR code e-Module test. The instruments used are questionnaires, the data used in the study at analysis using descriptive statistics in the form of presentation. The validity of the materials by 89.17%, the validity of the median expert by 83.33%, and the validity of the linguist by 88.71% valid criteria. Thus concludes that the e-Module based on the QR code developed is declared valid with an average of 87.07%.